2017
DOI: 10.3390/ma10060616
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive Inspection of Impact Damage in Composite Aircraft Panels by Ultrasonic Guided Waves and Statistical Processing

Abstract: This paper discusses a non-destructive evaluation (NDE) technique for the detection of damage in composite aircraft structures following high energy wide area blunt impact (HEWABI) from ground service equipment (GSE), such as heavy cargo loaders and other heavy equipment. The test structures typically include skin, co-cured stringers, and C-frames that are bolt-connected onto the skin with shear ties. The inspection exploits the waveguide geometry of these structures by utilizing ultrasonic guided waves and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…In MD FRP composite laminates, matrix yielding/cracking and interface delamination are observed as the early damage mechanisms due to very low stiffness/strength properties of the matrix and interface (10%-20%) compared to the fiber properties level [10,[47][48][49][50]. In addition, the variation of through-thickness lamina orientations in an MD composite facilitates matrix failure and multi-delamination events at the early stage of the loading [10,43,45,51]. In some cases, the MD FRP composite structure was able to sustain up to 10-fold higher loading above the level corresponding to the onset of matrix and interface damages [10,43,45].…”
Section: Introductionmentioning
confidence: 99%
“…In MD FRP composite laminates, matrix yielding/cracking and interface delamination are observed as the early damage mechanisms due to very low stiffness/strength properties of the matrix and interface (10%-20%) compared to the fiber properties level [10,[47][48][49][50]. In addition, the variation of through-thickness lamina orientations in an MD composite facilitates matrix failure and multi-delamination events at the early stage of the loading [10,43,45,51]. In some cases, the MD FRP composite structure was able to sustain up to 10-fold higher loading above the level corresponding to the onset of matrix and interface damages [10,43,45].…”
Section: Introductionmentioning
confidence: 99%
“…These results are easily available in many journals and selected recent examples of this research can be found in references [11][12][13][14][15][16][17][18]. Similar papers dealing with problems on a slightly bigger scale (aircraft panels) are available in references [19,20].…”
Section: Introductionmentioning
confidence: 93%
“…The feature extraction of transient response can be performed by exploiting the characteristics of the signal such as root mean square (RMS), variance, kurtosis, skewness [13] etc. However, previous researches in RFID based sensing only focus on transient response and first order differential features, e.g.…”
Section: Rfid Technology Is a Passive Wireless Communication Technolomentioning
confidence: 99%